Qualidade, perfil de compostos fenólicos e potencial funcional de variedades de fava (Phaseolus lunatus L. - Nascimento, Ricardo de Sousa (2016)
The lima bean (Phaseolus lunatus L.) is a plant originated in Central America, belonging to family Fabaceae of the genus Phaseolus that fits well in most areas and climatic features drought-tolerance and to warm weather. This leguminous is cultivated in the northeastern region of Brazil in function its of nutritional value, being considered a good source of carbohydrate, proteins, fiber, vitamins, minerals, flavonoids, anthocyanins, polyphenols and antioxidant compounds. The main form of consumption and preparation of the lima bean occurs with grains still green or dried cooked under high temperatures. This process contributes to the reduction of anti-nutritional compounds and assists in the consumption improving the taste and the palatability, increases the availability of nutrients and leads to a series of changes in the physical and chemical characteristics. In this way, studies are required to determine the factors of pre and post cooking that more influence the preference, especially those determinants to the flavor. An important tool to assess the choice of different varieties of lima bean for the consumers is the descriptive quantitative sensory analysis. In this context, this work was developed, covering the above aspects explained, being divided into two chapters. In the Chapter I was evaluated the effect of cooking on the quality and sensorial aspects of different lima bean varieties raw and cooked. This experiment was conducted at completely randomized design using five lima bean varieties denominated in the region as Cearense’, ‘Fava Branca’, ‘Orelha de Vó’, ‘Rosinha’ and ‘Roxinha’ analyzing in two conditions (raw and cooked). The lima bean varieties presented differences in their chemical and physico-chemical composition; the cooking process promotes several alterations in the physical and physico-chemical properties of all varieties studied, resulting in qualitative and quantitative changes in the total composition of the cooked grains. In the Chapter II were evaluated the bioactive compounds and antioxidant activity of the different lima bean varieties, indicating the main alterations arising from the grain cooking, as well as composition of juice. This search was realized in two tests: 1) Characterization of the raw grains of five lima bean varieties; 2) Evaluation of cooked lima bean, realized in factorial scheme 5 x 2, being 5 lima bean varieties and 2 portions after cooking (grains and juice). The lima bean varieties with darkest coloration, ‘Rosinha’ and ‘Roxinha’, present higher content of phenolic acids, anthocyanin and flavonoids, as well as antioxidant activity in the composition of its raw, cooked grains and juice. It was found a decrease in bioactive compounds caused by the cooking process and accumulation of them in the juice. In addition, we detected, by HPLC, 2.5-dihidoxibenzoic acid, 3.4-dihidoxibenzoic acid and 4 4-hidroxibenzoic acid as main phenolic acids present in their composition of all varieties with prominence to ‘Rosinha’ and ‘Roxinha’. The catechin, chrysin and myricetin were the main flavonoids detected in all lima bean varieties.